1986
DOI: 10.1002/j.1939-4640.1986.tb00932.x
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Spermatic Granulomas and Their Relation to Testis Weight after Vasectomy and Vasovasostomy in Lewis Rats

Abstract: The occurrence of spermatic granulomas of the vas deferens was studied in Lewis rats at intervals up to 7 months after vasectomy or vasectomy followed 3 months later by vasovasostomy. The incidence of granuloma progressed with time to involve one or both tracts in 100% of vasectomized rats. In addition, the majority of animals developed new granulomas after vasovasostomy, even though fluid flow through the reconnected vas deferens was demonstrated in vitro. When individual tracts were analyzed, the weight of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…The best known of the systemic consequences is a rise in antisperm antibodies, which occurs after vasectomy in virtually all species studied (Alexander and Anderson, 1979). Local changes have been reported in most parts of the reproductive tract, including the testis (Bedford, 1976;Fawcett, 1979;Jarow et al, 1985;Flickinger et al, 1987), efferent ducts (Alexander, 1972;Flickinger, 1982), epididymis (Flickinger, 1972(Flickinger, , 1982Alexander, 1973;Miller and Killian, 1987), and vas deferens (Heidger and Sawatzke, 1977;Hamadinia et al, 19801, and spermatic granulomas have been observed to form where the tract has ruptured (Neaves, 1975;Bedford, 1976;Flickinger et al, 1986). Testicular lesions have attracted the most attention (Flickinger, 19851, because of their potential influence on fertility if reversal of vasectomy is desired at a later time.…”
Section: Flammation Ratmentioning
confidence: 95%
“…The best known of the systemic consequences is a rise in antisperm antibodies, which occurs after vasectomy in virtually all species studied (Alexander and Anderson, 1979). Local changes have been reported in most parts of the reproductive tract, including the testis (Bedford, 1976;Fawcett, 1979;Jarow et al, 1985;Flickinger et al, 1987), efferent ducts (Alexander, 1972;Flickinger, 1982), epididymis (Flickinger, 1972(Flickinger, , 1982Alexander, 1973;Miller and Killian, 1987), and vas deferens (Heidger and Sawatzke, 1977;Hamadinia et al, 19801, and spermatic granulomas have been observed to form where the tract has ruptured (Neaves, 1975;Bedford, 1976;Flickinger et al, 1986). Testicular lesions have attracted the most attention (Flickinger, 19851, because of their potential influence on fertility if reversal of vasectomy is desired at a later time.…”
Section: Flammation Ratmentioning
confidence: 95%
“…These show features of a chronic inflammatory process with a fibrous shell, lymphocytes, and plasma cells surrounding a semisolid core of degenerating sperm and phagocytes (Flickinger et al, 1986(Flickinger et al, , 1995. Once sperm had arrived in the epididymis between 42 and 56 days (Scheer and Robaire, 1980;Robaire and Hermo, 1988), the majority of postpubertal rats with epididymal ligations 56 days or…”
Section: Spermatic Granulomasmentioning
confidence: 97%
“…Autoimmune response to sperm antigens is an established fact, and is the basis for infertility in men undergoing vasectomy (Alexander 1975, Alexander & Anderson 1979, Rose & Lucas 1979, Tung & Menge 1985, Flickinger et al 1986.…”
Section: Development Of Type 1 Microcanalmentioning
confidence: 99%